Coherent polarization locking of multimode beams in a diode bar - Purnawirman, P. (2011)
We demonstrate coherent polarization locking of multimode beams from four broad area emitters in a diode bar. The beams are overlapped into single output by using walk-off crystals and waveplates while their phases are locked via polarization discrimination. Coherent locking of multimode beams enabled power scaling of coherent diode output while retaining beam quality of single emitter. We obtained power of 7.2 W with M2 of 1.5 x 11.5 from a 980 nm diode laser. This corresponds to brightness improvement of more than an order of magnitude.